Cultural connections and cultural ceilings: exploring the experiences of Aboriginal Australian sport coaches. Issue 3 (27th May 2019) - Bennie, Andrew; Apoifis, Nicholas; Marlin, Demelza; Caron, Jeffrey G.
Abstract: Sport researchers have begun to appreciate the perspectives and experiences of Aboriginal athletes in various global communities, yet little is known about Aboriginal sport coaches. Considering sport can play a positive social, psychological, and physical role in the lives of Aboriginal people, it is problematic that there is a dearth of academic literature exploring the narratives of Aboriginal coaches. This is one of the first studies to specifically explore Aboriginal Australian peoples' experiences in sport coaching roles. Using a socio-ecological framework to frame our discussions, we share the insights of 28 Aboriginal Australian sport coaches from a variety of team and individual sports as they describe an array of factors that facilitated and impeded their sport coaching journeys. By shedding light on these narratives this paper performs two main tasks. First, taking a qualitative approach, it gives agency and voice to Aboriginal people, long-neglected in academic sports scholarship. Second, it provides insights for coaches, athletes, academics, policy-makers, and sporting organisations interested in enhancing opportunities and developing pathways for Aboriginal people in sport coaching roles.